Effects of prefrontal cortical stimulation on aggressive and antisocial behavior: A double-blind, stratified, randomized, sham-controlled, parallel-group trial - Ling, Shichun (Journal of experimental criminology, 2020)
This study examines the influence of high-definition transcranial direct current stimulation (HD-tDCS) of the prefrontal cortex (PFC) on aggressive behavior and antisocial intentions, and provides an updated meta-analysis of prior studies.